2010
DOI: 10.1097/pas.0b013e3181f2ee0b
|View full text |Cite
|
Sign up to set email alerts
|

Clear Cell Tubulopapillary Renal Cell Carcinoma: A Study of 36 Distinctive Low-grade Epithelial Tumors of the Kidney

Abstract: Recently several low-grade renal cell tumors, distinct from those recognized by the 2004 World Health Organization classification of renal tumors, have been described. These tumors had similar clinicopathologic features, being low-stage tumors with cystic, tubuloacinar, and/or papillary architecture. The tumor cells were low grade with variable amounts of clear cytoplasm that was positive for cytokeratin 7 (CK7), but negative for CD10. Genetic changes characteristic of clear cell or papillary renal cell carcin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

22
233
4
7

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 180 publications
(270 citation statements)
references
References 30 publications
22
233
4
7
Order By: Relevance
“…[33][34][35] Comparison to Clear Cell Papillary Renal Cell Carcinoma It has been hypothesized that these renal cell carcinomas with smooth muscle stroma are part of the morphological spectrum of clear cell papillary renal cell carcinoma. 13 In keeping with such a possibility, we found the immunohistochemical profile of these two tumor types to overlap, including labeling for carbonic anhydrase IX (sometimes with a 'cup-shaped' staining pattern 8 ), CK7, 6,8,10 and cytokeratin 34bE12 8 and negative reactivity for AMACR. 6,8,10 As a point of contrast, the tumors in this study showed more diffuse labeling for CD10 than expected of clear cell papillary renal cell carcinoma.…”
Section: Discussionsupporting
confidence: 54%
See 4 more Smart Citations
“…[33][34][35] Comparison to Clear Cell Papillary Renal Cell Carcinoma It has been hypothesized that these renal cell carcinomas with smooth muscle stroma are part of the morphological spectrum of clear cell papillary renal cell carcinoma. 13 In keeping with such a possibility, we found the immunohistochemical profile of these two tumor types to overlap, including labeling for carbonic anhydrase IX (sometimes with a 'cup-shaped' staining pattern 8 ), CK7, 6,8,10 and cytokeratin 34bE12 8 and negative reactivity for AMACR. 6,8,10 As a point of contrast, the tumors in this study showed more diffuse labeling for CD10 than expected of clear cell papillary renal cell carcinoma.…”
Section: Discussionsupporting
confidence: 54%
“…13 In keeping with such a possibility, we found the immunohistochemical profile of these two tumor types to overlap, including labeling for carbonic anhydrase IX (sometimes with a 'cup-shaped' staining pattern 8 ), CK7, 6,8,10 and cytokeratin 34bE12 8 and negative reactivity for AMACR. 6,8,10 As a point of contrast, the tumors in this study showed more diffuse labeling for CD10 than expected of clear cell papillary renal cell carcinoma. 10 In our experience, clear cell papillary renal cell carcinoma usually shows an entirely negative reaction for CD10 or apical labeling of only the cyst-lining cells; however, others have occasionally observed focal labeling for CD10 in non-cystic areas.…”
Section: Discussionsupporting
confidence: 54%
See 3 more Smart Citations